Financial Performance of Ultra-Micro Banks Before and During the Covid-19 Pandemic (A Case Study of BTPN Syariah) - Fadillah, Junis; Yandri, Pitri (Green Publisher Indonesia, 2025)
The COVID-19 pandemic has significantly impacted financial performance across all economic sectors, including ultra-micro Islamic banking institutions such as BTPN Syariah, which specializes in serving underprivileged productive communities. This study examines the differences in BTPN Syariah’s financial performance before (2017–2019) and during (2020–2022) the COVID-19 pandemic in Indonesia. Utilizing secondary data from monthly financial statements published by BTPN Syariah, this research employs a paired sample t-test analysis using SPSS software to compare six key financial performance indicators: Return on Assets (ROA), Return on Equity (ROE), Capital Adequacy Ratio (CAR), Operating Costs to Operating Income ratio (BOPO), Non-Performing Financing (NPF), and Financing to Deposit Ratio (FDR). The results indicate significant differences in banking financial performance between the pre-pandemic and pandemic periods, with CAR showing notable improvement due to a strategic Initial Public Offering (IPO), while ROA and ROE experienced temporary declines followed by gradual recovery. These findings contribute to understanding the resilience mechanisms of Islamic ultra-micro banking institutions during crisis periods and provide insights for policymakers and practitioners in developing countercyclical strategies for future economic disruptions.